Surface Treatment Strategies to Enhance Adhesive Bond Strength for AA7075-T6 in Aerospace Applications - Hassan Ejaz; Abdul Wahab; Romail Saeed; Ammad Ahmed; Manzar Masud (Engineering Proceedings)
Adhesive joints play a crucial role across industries, such as aerospace, automotive, and construction, offering distinct advantages over traditional mechanical fastening methods. This study comprehensively evaluates ten surface treatments, ranging from solvent degreasing to mechanical abrasion, chemical etching, and electrochemical anodization on lap shear strength of AA 7075-T6 joints bonded with Huntsman Araldite 2011 epoxy with an ultimate goal to find the optimum surface treatment. Each treatment’s efficacy was assessed through ASTM D1002 standards using a Universal Testing Machine (UTM). Mechanical treatments, specifically sandblasting, significantly increased bond strength by up to 103.35%, whereas chemical treatment Dichromate/Sulfuric acid etching showed a maximum strength improvement of 77.9%. Electrochemical anodization, especially phosphoric-boric-sulfuric acid anodizing (PBSAA), achieved the highest strength improvement of 109%. Sandblasting emerged as the most cost-effective and efficient method for strength enhancement, whereas PBSAA is recommended for applications requiring superior strength, durability, and protection against environmental factors, which are potential requirements in aerospace applications.